Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic